2013
DOI: 10.1080/09540121.2013.841829
|View full text |Cite
|
Sign up to set email alerts
|

The importance of caregivers in the outcome of pediatric HIV management, Mombasa, Kenya

Abstract: We assessed programmatic gaps that prevent the optimal treatment of pediatric HIV infection despite free antiretroviral care in Kenya. Of 626 HIV-infected Kenyan children, the median age was five years, 54% were male and the mortality rate was 3.2 per 100 person-years. A total of 380 (61%) children initiated antiretroviral therapy (ART) during the study period. Among the 246 children who never started ART, 129 (52%) met the criteria for ART initiation. Immunologic failure occurred in 20% of children who receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
1
10
1
Order By: Relevance
“…Overall, these findings corroborate other research that emphasized the importance of families, psychosocial environments and caregiver characteristics on ART adherence and well-being of younger children living with HIV in SSA [6,17,38,39] and among perinatally infected youth in the United States [4042]. While the need for caregiver involvement is undisputed when discussing medication adherence among children and young adolescents (<14), the role of families and caregivers has been explored less in relationship to older ALHIV.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, these findings corroborate other research that emphasized the importance of families, psychosocial environments and caregiver characteristics on ART adherence and well-being of younger children living with HIV in SSA [6,17,38,39] and among perinatally infected youth in the United States [4042]. While the need for caregiver involvement is undisputed when discussing medication adherence among children and young adolescents (<14), the role of families and caregivers has been explored less in relationship to older ALHIV.…”
Section: Discussionsupporting
confidence: 88%
“…18,58 An HIV positive caretaker could also be afraid of disclosing their child’s or their status for fear of discrimination. 20 In our study, univariate analyses demonstrated that the caretaker’s identity, parent or other, is not associated with LTFU among children, but children whose caretaker had positive or unknown HIV status were more likely to be LTFU, although this findings was not significant in the multivariate analysis, possibly due to a lack of power. Adherence counseling tailored to the caretaker may be an underappreciated factor affecting treatment outcomes among HIV-infected children living in Tanzania and similar settings.…”
Section: Discussioncontrasting
confidence: 64%
“…Adherence counseling tailored to the caretaker may be an underappreciated factor affecting treatment outcomes among HIV-infected children living in Tanzania and similar settings. 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having a parent or caregiver present at clinical visits appears to be protective of adherence and treatment outcomes among adolescents (18, 19). Adherence has been inconsistently associated with gender (17, 18, 20, 21) and orphan/caregiver status (2123). Lack of caregiver involvement was incorporated into our definition of a positive PSC as we classified non-completion of the PSC as a positive score.…”
Section: Discussionmentioning
confidence: 99%